Agent-based throughput response in presence of node and/or link failure (on demand) for circuit switched telecommunication networks - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2004)
An attractive feature of an agent-based control system is being studied in this paper, with respect to network throughput for a certain amount of traffic and applied to a synchronous digital hierarchy network. Algorithmically complex problems like routing a call in a network, need to be faced with a dynamically adaptive approach such as agent-based probabilistic routing. The performance of a decentralized-based routing scheme that is subject to link and/or node failures is examined while agents are moving across the network and define a cost effective path from a source to a destination. Agent-based routing scheme is proved to increase the service rate and throughput response of the system with significant reduction in call failures. Through various newly introduced metrics and simulation of the proposed scenario, we have shown that agent-based routing offer us a decentralized control in the network and an efficient way to increase overall performance.
Keywords: Decentralized schemes; Ant system; Swarm intelligence; Intelligent mobile agents